Periódicos científicos de Direito e o uso de mídias sociais: presença, visibilidade e desempenho - Rômulo Mansur Lauar Júnior (2024)
This study proposes to investigate how academic journals in the area of Law have used social media to expand the dissemination of academic and scientific production in this field. This is a study with a qualitative and quantitative approach (quali-quanti) of a descriptive nature, which sought to understand the phenomena by translating the data into metrics and indicators. Regarding the procedures, a brief bibliographical research was carried out and data was collected on the presence, activity and performance of magazines on social media with qualitative analysis of the information obtained in terms of visibility, influence and engagement and reputation. To this end, a survey was carried out of scientific law journals with Qualis A1 extract in the 2013- 2016 extract on the Sucupira Platform and their presence and performance on the main social media (Facebook, Instagram and Twitter). Although 127 Qualis A1 publications were found on the Sucupira Platform, only 19 had profiles on social media (15.74%), 12 of which were on Facebook, seven on Instagram and five on Twitter. As for visibility, seen as the ability to reach the content posted, the magazines analyzed total 27,421 fans on Facebook, 16,685 on Instagram and 17,044 on Twitter. The influence indicator, directly linked to the mobilization capacity of the entity that publishes content in the analyzed accounts, proved to be extremely low or non- existent. Engagement, in turn, revealed that few magazines received interactions on their posts. With the low performance of previous indicators, reputation often indicates zero or negative performance. Among the research findings is the perception that there has been a setback in the use of these spaces for scientific dissemination.